Fossil fuel energy and environmental performance in an extended STIRPAT model. (15th May 2021) - Gani, Azmat
Abstract: Recent reports by the Intergovernmental Panel on Climate Change (2018 and 2019) have revealed that world's human activities have contributed to around 1 °C of global warming above the pre-industrial levels (expected to reach 1.5 °C between 2030 and 2052) with the burning of fossil fuel contributing to over three-quarters of world's emissions. Rising demand for energy is expected to add another 39 billion tonnes of carbon-dioxide, threatening the climate action plan of achieving net-zero by 2050. Given the expected worsening of emissions from fossil fuels' burning, this paper's main objective is to empirically examine the supply-side effect of energy generation from fossil fuels (coal, natural gas and oil) on environmental quality. In doing so, an extended Stochastic Impacts by Regression on Population Affluence and Technology (STIRPAT) model is adopted that controls for a range of economic, social and institutional factors. The panel data estimation technique is applied to the model that includes a balanced panel of 59 countries using coal, 77 countries using gas and 96 countries using oil for 2002 to 2016. The results revealed coefficient coal is negative and statistically significant at the 1 per cent level ( α  = −0.052 with ρ  = 0.01) and oil is negative and statistically significant at 5 per cent level ( α  = −0.020 with ρ  = 0.05). These results support supply-side energy generation through the burning of coal and oil as vital contributors to environmental quality degradation. Other than confirming the Environmental Kuznets Curve (EKC) effect, forest cover, schooling, the rule of law and nations commitments to international environmental treaties are other strong correlates of environmental performance. The findings also revealed strong adverse effects of agriculture and industrial intensification on environmental quality. The main conclusion is the urgency for the worlds fossil fuel energy-dependent countries to transit from fossil fuel energy to the production of frontier renewable (cleaner forms) sources of energy to minimise degradation of the environment. Other than exploring supply-side carbon mitigation policies, there is a need for active co-operation of all countries of the world in the enforcement of international treaties to minimise further environmental damage. Highlights: The effect of fossil fuel energy production on environmental quality is studied. The sustainable energy and environmental outcomes framework is adopted. The analysis uses the STIRPAT model for the period 2002 to 2010. Coal and oil led energy production are associated with environmental degradation. The adoption of sustainable energy production policies is essential.